La tenzone fra Costantino Rodio e Teodoro Paflagone - CARROZZA, Marco (Byzantina Symmeikta, 2024)
This paper provides a critical edition, translation and literary remarks of the thirteen iambic poems that make up the poetic dispute among Constantine Rhodius and Theodore Paphlagon, with the primary aim of highlighting the language and offensive strategies typical of the present λογικὸς ἀγών and, in general, of the Byzantine scoptic poetry, identifying, as far as possible, genre analogies with other satirists of the same era.